Accuracy and Coordination of Spatial Frames of Reference during the Exploration of Virtual Maps: Interest for Orientation and Mobility of Blind People?. (13th September 2012) - Simonnet, Mathieu; Vieilledent, Stéphane
Abstract : Even if their spatial reasoning capabilities remain quite similar to those of sighted people, blind people encounter difficulties in getting distant information from their surroundings. Thus, whole body displacements, tactile map consultations, or auditory solutions are needed to establish physical contacts with their environment. Therefore, the accuracy of nonvisual spatial representations heavily relies upon the efficiency of exploration strategies and the ability to coordinate egocentric and allocentric spatial frames of reference. This study aims to better understand the mechanisms of this coordination without vision by analyzing cartographic exploration strategies and assessing their influence on mental spatial representations. Six blind sailors were immersed within a virtual haptic and auditory maritime environment. They were required to learn the layout of the map. Their movements were recorded and we identified some exploration strategies. Then they had to estimate the directions of six particular seamarks in aligned and misaligned situations. Better accuracy and coordination were obtained when participants used the "central point of reference" strategy. Our discussion relative to the articulation between geometric enduring representations and salient transient perceptions provides implications on map reading techniques and on mobility and orientation programs for blind people.